Crime and the transition to marriage. The roles of gender and partner's criminal involvement - Christian Weisæth Monsbakken; Torkild Hovde Lyngstad; Torbjørn Skardhamar (Statistics Norway, Research Department, 2012)
Several previous studies have argued that marriage leads to a decline in criminal propensity. Most of these studies have focused on men and have given little attention to the characteristics of their partner and events related to changes in offending. In this article, we use Norwegian registry data to study changes in the criminal propensity for all persons who married between 1995 and 2001 (117,882 women and 120,912 men). We link data on individuals to data on their marital partners and obtain information on partners' criminal histories. We find that the changes in offending rates related to marriage are anticipatory and strongest for men. The changes in offending vary substantially by partner's criminal history.
Keywords: J12; K14; K49; 330; marriage; crime; social control; gender; assortative mating